2023
DOI: 10.1038/s42003-023-04836-9
|View full text |Cite
|
Sign up to set email alerts
|

Fine-mapping of retinal vascular complexity loci identifies Notch regulation as a shared mechanism with myocardial infarction outcomes

Abstract: There is increasing evidence that the complexity of the retinal vasculature measured as fractal dimension, Df, might offer earlier insights into the progression of coronary artery disease (CAD) before traditional biomarkers can be detected. This association could be partly explained by a common genetic basis; however, the genetic component of Df is poorly understood. We present a genome-wide association study (GWAS) of 38,000 individuals with white British ancestry from the UK Biobank aimed to comprehensively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 86 publications
3
3
0
Order By: Relevance
“…Finally, reverse MR suggested that circulating FOXO3 levels may be a blood biomarker for changes in retinal vascular D f . The findings from the D f GWAS meta-analysis were consistent with previous genetic analyses on retinal D f , thus, supporting the biologically coherent relationships of D fassociated variants with various ocular and cardiovascular traits and diseases 5,10,35 . Interestingly, we found that several loci were also associated with either cardiovascular risk factors (e.g., hypertension, and dyslipidaemia) or diseases (e.g., coronary artery diseases), as well as inflammatory and immune responses 20,21,22,23,24,25,26,27,28 .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Finally, reverse MR suggested that circulating FOXO3 levels may be a blood biomarker for changes in retinal vascular D f . The findings from the D f GWAS meta-analysis were consistent with previous genetic analyses on retinal D f , thus, supporting the biologically coherent relationships of D fassociated variants with various ocular and cardiovascular traits and diseases 5,10,35 . Interestingly, we found that several loci were also associated with either cardiovascular risk factors (e.g., hypertension, and dyslipidaemia) or diseases (e.g., coronary artery diseases), as well as inflammatory and immune responses 20,21,22,23,24,25,26,27,28 .…”
Section: Discussionsupporting
confidence: 86%
“…We found nominally significant negative correlations of D f with C-reactive protein (r g = -0.13 ± 0.05), atherosclerosis (r g = -0.24 ± 0.03), coronary artery disease (r g = -0.12 ± 0.06), stroke (r g = -0.23 ± 0.09), and a positive correlation with longevity (r g = 0.12 ± 0.06) (Suppl Table 6). Such findings were consistent with the findings that we previously reported for analysis conducted in a subset of UKBB individuals 10 .…”
supporting
confidence: 93%
See 2 more Smart Citations
“…They showed that their technique can work as a generalized approach for retinal morphology analyses. Of note, such hybrid models can be impactful, since retinal imaging is not only used to assess ophthalmic pathologies, but also changes in retinal morphologies that may occur early in a broad spectrum of diseases, such as Alzheimer's [154], cardiac pathologies [155], cerebral small vessel disease [156] and others. Wang et al have proposed the MsTGANet, a UNet model enhanced with a Transformer block that consists of a series of multi-head self-attention mechanisms incorporated in the encoder, to capture both local and global pixel interactions early in the learning process [45].…”
Section: Segmentationmentioning
confidence: 99%